BRANDING SATUAN PAUD SEJENIS â€œGEMBIRAâ€ PAKUNCEN YOGYAKARTA - Rio Septian (CILPA, 2020)
This research was initiated from the concern of Gembira ECDâ€™s management due to the absence of children in the early age that participated in the education program in Singosaren Lor Village and its surrounding area whether in the level of Kindergarten, Playgroup or even in the daily care. This condition occurs due to the local economic condition. In designing the branding of Gembira ECD, the author aims are: 1) designing the branding concept of Gembira ECD in accordance with the image and particular characteristic of this institution, 2) inventing effective and efficient branding design for the community especially the parents of 0-6 years old children, 3) visualizing the design concept that able to expose the institution branding of Gembira ECD.Â Â Â  The art creation concept of this thesis is to invent the institution branding of Gembira ECD by using STP and SWOT analysis which resulted in the target or purpose audience. Based on this analysis, the product's designs were created to promote Gembira ECD through logo creation, nameplate, flyer, id-card, company profile, folding-display desk, sports uniform, presence book, name card, x-banner, table calendar, and web design. Through this branding concept, the branding design was created in accordance with design layout technique, appropriate media concept and the design concept that conceive the branding design applications which are the primary and supporting/secondary media that also conceive creative strategies.Â Â  The branding design result for Gembira ECD produces several designs such as logo nameplate, flyer, id-card, company profile, folding-display desk, sports uniform, presence book, name card, x-banner, table calendar, and web design. Based on this branding concept, the author has invented the branding design that based on design layout technique, appropriate media concept and the design concept that conceive the branding design applications with creative strategies. The branding design was visualized in accordance with invention/creation concept through vector technique by using Coreldraw X7 software.Â  Â